Diabetes Mellitus is Associated With Mortality in Acute Pancreatitis. Issue 2 (February 2018) - Huh, Ji Hye; Jeon, Hosung; Park, Sun Min; Choi, EunHee; Lee, Geun Sook; Kim, Jae Woo; Lee, Kyong Joo
Abstract : Background and Aim: Predicting severe pancreatitis is important for early aggressive management of patients with acute pancreatitis (AP). Despite the established role of diabetes mellitus (DM) in the risk of AP, the impact of DM on the clinical outcome in AP has not been fully elucidated. The objective of this study was to assess the risk of mortality and severity in AP among patients with type-2 DM. Methods: Patients diagnosed with first attacks of AP were enrolled from January 2013 to June 2015. Results: A total of 201 patients (63.2% male, mean age, 59.4 y) with AP were included. Etiologies included gallstones (51.2%), alcohol (37.3%), hypertriglyceridemia (2%), and idiopathic causes (9.5%). There were 54 AP patients (26.9%) with type-2 DM. Severity indices in AP, such as Atlanta Classification (severe), Ranson score, and Bedside Index of Severity in Acute Pancreatitis, were higher in subjects with DM than those without DM. Prevalence of intensive care unit admission and mortality were higher in AP patients with DM compared with those without DM. The association between DM and increased risk of mortality in AP remained statistically significant even after adjustments for confounding factors and Atlanta Classification (odds ratio, 7.76, 95% confidence interval, 1.26-47.63, P =0.027). Conclusions: Type-2 DM was associated with severity and increased mortality in patients with AP. Our findings provide evidence of the potential role of DM in the pathogenesis and management of severe AP.